2000
DOI: 10.1037/0894-4105.14.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Aging, episodic memory feeling-of-knowing, and frontal functioning.

Abstract: Groups of normal old and young adults made episodic memory feeling-of-knowing (FOK) judgments and took 2 types of episodic memory tests (cued recall and recognition). Neuropsychological tests of executive and memory functions thought to respectively involve the frontal and medial temporal structures were also administered. Age differences were observed on the episodic memory measures and on all neuropsychological tests. Compared with young adults, older adults performed at chance level on FOK accuracy judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 76 publications
8
122
2
7
Order By: Relevance
“…Along the same lines, aging research attributes memory decline in old adults, especially episodic memory impairments to the decline in executive functions as well as a frontal cortex impairment (Souchay & Isingrini, 2004;Souchay, Isingrini, & Espagnet, 2000;see West, 1996 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, aging research attributes memory decline in old adults, especially episodic memory impairments to the decline in executive functions as well as a frontal cortex impairment (Souchay & Isingrini, 2004;Souchay, Isingrini, & Espagnet, 2000;see West, 1996 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Despite consistent deficits in episodic memory, preservation of episodic FOK ratings has been reported MacLaverty & Hertzog, 2009), implying that older adults are aware of their lowered memory performance and incorporate this knowledge into their memory judgments. However, a number of studies have also found evidence of an impairment in episodic FOK accuracy (Perrotin et al, 2006;Souchay et al, 2000;Thomas et al, 2011). These later studies thus suggest that as memory performance declines, so does the ability to accurately monitor the contents of memory, leading to errors in judgments.…”
Section: Introductionmentioning
confidence: 96%
“…Research involving frontal lobe patients has repeatedly shown an impairment in episodic FOK accuracy (Janowsky et al, 1989;Pinon et al, 2005;Schnyer et al, 2004; but see Pannu et al, 2005), indicating that this region plays a vital role in assessing future retrieval for episodic information. In aging, a clear link has been demonstrated between executive function and episodic FOK accuracy (Perrotin et al, 2006;Perrotin et al, 2008;Souchay et al, 2000), with deficits in executive function associated with deficits in episodic FOK resolution. This again emphasises the importance of the frontal lobes for successful monitoring of memory, as executive function is primarily associated to frontal lobe regions (Courtney et al, 1996;Gold et al, 1996;Jonides et al, 1993;McCarthy et al, 1994;Owen et al, 1996;Petrides et al, 1993;Smith & Jonides, 1999;Smith et al, 1995;Sweeney et al, 1996), which show the earliest and greatest age-related atrophy (Raz, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…30, nº 1 (enero) En el caso de la memoria episódica, el deterioro aparece fundamentalmente en: a) tareas que implican un esfuerzo de codificación y recuperación de la información importante, esto es, cuando la ejecución de esa tarea requiere de la memoria de trabajo (Belleville et al, 2006;Clarys et al, 2007;Souchay, Isingrini, & Espagnet, 2000); y b) el recuerdo de hechos recientes o prospectivos ligados a las acontecimientos de la vida diaria del sujeto: recordar nombres de personas, números de teléfono, dónde han dejado sus objetos, etc. (Montejo, & Montenegro, 2006).…”
Section: Introductionunclassified